From the law of the jungle to partnership? The bumpy road to new producer-supplier relations in the automotive industry. The example of a bodywork and assembly plant - Heiderose Kilper; Jürgen Schmidt-Dilcher (Institut Arbeit und Technik (IAT), 2000)
Since around a decade, the automobile industry is undergoing a dramatic turnaround. New strategies for marketing and producing are considered as trigger pulses for the emergence of different inter-firm relations between customers and suppliers in the car industry's production complex. The development of partnership between OEMs and suppliers asks from both sides new approaches, new routines in dealing with each other as well as new modes of thinking and acting. The following study reflects our understandings and experiences, we got by the project "Optimization of the sourcing and production strategies between suppliers and producer". A result is, that you can observe concepts and approaches of re-shaping of communication and co-operation, that reflect the completely different demands in the sourcing and production process. But their potentials can be tested and developed only very steadily. In reality, instruments and procedures of coordination and regulation as well as behaviours are dominating, which ground on obsolete power constellations and are minted by OEMs hegemony. Above all, the intented project's goal "development and testing of partnership in communication and co-operation in the relationships between the car factory and its suppliers" is determinated by centralized decision making-structures and by strategies of the car-company, which are partly contradictionary. – – Die Automobilindustrie befindet sich seit etwa einem Jahrzehnt in einer dramatisch zu nennenden Umwälzung. Veränderte Markt- und Produktionsstrategien gelten als Auslöser für die Entwicklung einer neuen zwischenbetrieblichen Arbeitsteilung zwischen Herstellern und Zulieferern im Produktionskomplex Automobil. Die Entwicklung partnerschaftlicher Hersteller- Zulieferer-Beziehungen erforderte von Herstellern wie Zulieferern ein Umdenken, andere Routinen im Umgang miteinander sowie neue Denk- und Verhaltensweisen. Resultat der vorliegenden Studie, die Einsichten und Erfahrungen aus dem Projekt 'Optimierung der Produktions- und Lieferbeziehungen zwischen Zulieferern und Hersteller' bilanziert, ist, dass sowohl bei dem beteiligten Automobilhersteller als auch auf Seiten seiner involvierten Zulieferer Konzepte und Ansätze zu einer partnerschaftlichen Neugestaltung der Kommunikations- und Kooperationsformen zu verzeichnen sind, welche die tiefgreifend veränderten Anforderungen im Produktions- und Belieferungsprozess reflektieren. Ihre Potentiale können aber erst allmählich erprobt und entfaltet werden, weil in der Alltagspraxis nach wie vor Koordinations
Keywords: 330